Perencanaan Pengembangan Usaha Tani Perhutan Kerakyatan Di Daerah Tangkapan Gumbasa Bagian Hulu, Donggala, SULTENG (Studi Kasus Sub-sub Daerah Aliran Sungai Toranda) - Hariyono (Jurnal Bakti Agribisnis, 2017)
The Research amed to determind policy introduce social forestry management development as a sustainable in Gumbasa Catchment Area – Donggala – Central Sulawesi. Research by case study from Subs Toranda Watershed,, included: social preference analysis for social forestry management development by MPE Approach, financial feasebility analysis by social economic method approach and soil erosion analysis by trial erosion approach, in cacao land use monoculture (traditional) 9% slope and 37%, cacao land use by SUPK/SFMU 10% slope and 38% and open land use 5% slope at all each 3 X so 15 sample unit. The result that social preference to choice commodity priorities farm develop SUPK/SFMU are; 1) Jati, 2) Mahoni3) Nantu/Nyatoh, 4) Cempaka, 5) Ebony, 6) Kemiri, 7) Avocado, Farm financial feasibility SUPK/SFMU by B/C ratio = 4,92 and IRR = 40% higher than cacao farm monoculture by B/C ratio 3,01 and IRR 35%. Cacao land use monoculture, SUPK/SFMU, open land use with erosion.Rate more from social erosion what can be accept (TSL). Land use erosion y cacao land use SUPK/SFMU can be reduce soil erosion 77,2% on slope “agak miring” and 74% on slope “agak curam” than cacao land use monoculture.